Cultivation of Oyster Mushrooms and Making Fried Oyster Mushrooms to Promote Health Efforts of Patients with Tuberculosis - Kumala, Tria Firza; Badrujamalludin, Asep; Budiana, Teguh Akbar (KnE Life Sciences, 2021)
Tuberculosis (TB) is still the world’s deadliest infectious killer. 10 new TB cases occured in the Cibiru area in 2017, all of whom were treated and cured. In 2018 there was an increase to 11 cases (Bandung City Health Profile, 2018). The purpose of this study is to help improve the soft skills and hard skills of health cadres and housewives in the Cibiru area in utilizing oyster mushroom cultivation by properly processing oyster mushrooms. Implementation methods based on the solutions to be developed and problems-solved methods. Oyster mushroom cultivation training is carried out twice for one month, with a focus on material on how to cultivate oyster mushrooms, counseling on processing crispy oyster mushrooms using Air Fryer and counseling on nutritional intake for TB patients, as well as guidance that is monitoring implementation. The results of these activities, it was found that the knowledge of health cadres and the community increased by more than 50%. The cultivation and processing of oyster mushrooms can increase economic income through the sale of processed oyster mushrooms using the Air Fryer method and get a profit of more than 10%. Keywords: Jamur tiram; Air fryer; Tuberculosis